A política nacional de formação continuada de professores da educação básica - 2004 - 2020. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
Doctoral dissertation presented to the Graduate Program in Education of the Universidade Estadual de Ponta Grossa, in the research line History and Education Policy. The theme of this PhD dissertation is the National Policy for Continuing Training of Basic Education Teachers. The general objective was to analyze the theoreticalepistemological foundations of the National Policy for Continuing Training of Basic Education Teachers, from 2004 to 2020, and its relations with the development, maintenance and intensification of the neoliberal project. The specific objectives outlined were as follows: a) to establish relations between capital, work, State and education and their determinants in the National Policy for Continuing Teacher Training; b) to identify the different theoretical-epistemological conceptions present in the National Policy for Continuing Training of Basic Education Teachers from 2004 to 2020; c) to indicate the perspective of Continuing Education of Teachers that concerns the working class, with a view to human emancipation, anchored in the documents of the National Association for the Training of Education Professionals (Associação Nacional pela Formação dos Profissionais da Educação – ANFOPE) as the main representative institution of teachers in the defense of a National Policy for Continuing Training linked to the emancipation of the education worker. The research was of qualitative nature, developed through documentary and bibliographical analysis, based on the historical and dialectical materialistic conception as it conceives that it apprehends the contradictions of the real. The historical-dialectical materialistic method is therefore characterized by the movement of thinking through the historical materiality of men’s lives in society. The theoretical framework was essentially drawn from the contributions of Friedrich Engels, Antonio Gramsci, István Mészáros, Karl Marx, among other authors who present elements that contribute to unveiling the fundamental laws that define the form of production of human life in society, through history. At the end of this study, it can be stated that the theoretical-epistemological foundations that support the National Policy for Continuing Training of Basic Education Teachers are sustained in the epistemology of practice, which, due to the form that it has been outlined, can be characterized by two synthesis categories: training as update and practice and flexible training. These two categories are predominant in the National Policy for Continuing Training throughout the analyzed period, which derives a conception of a teacher that is characterized as a practical-reflexive professional and a competent teacher. The centrality of continuing training lies in the development of skills and abilities, characterized by a set of technical and practical knowledge that aims to train teachers to solve the immediate and apparent problems, thus detached from their historical, political, economic and social determinations of the teaching praxis. When assuming the purpose of training the practical-reflexive and competent teacher, the National Policy for Continuing Training denies the teacher of Basic Education the possibilities of appropriation of theoretical knowledge, which, from the perspective of the historical-dialectical materialism, is to deny the understanding of determinations, mediations and contradictions that characterize the social totality. Denying theoretical knowledge means denying teaching, denying the teacher’s work as an intellectual, who holds the technical and practical domain of his/her craft, therefore it means to deny praxis. In this sense, it is advocated the thesis of the need to approve a National Subsystem of Training and Valorization of Teachers for Basic Education, when contemplating the articulation between Initial and Continuing Education, in the set of a National Education System, so that Continuing Training of Teachers is effectively a State policy and not a Government one, in order to ensure the overcoming of the fragmentation of the teaching professional training, as well as of contingency programs, devoid of solid, political and philosophical theoretical education, necessary and determining for an emancipating praxis.
Keywords: Políticas Educacionais; Política Nacional de Formação Continuada de Professores da Educação Básica; Fundamentos teórico-epistemológicos; Anfope; Education policies; National Policy for Continuing Training of Basic Education Teachers; Theoretical-epistemological foundations; ANFOPE; CNPQ::CIENCIAS HUMANAS::EDUCACAO